High-Throughput Determination of Mycobacterium smegmatis Protein Complex Structures - Kirykowicz, Angela Mary (Department of Integrative Biomedical Sciences (IBMS), 2019)
Tuberculosis (TB) is an endemic health-crisis, particularly in sub-Saharan Africa. The rise of multiand extensively-drug resistant Mycobacterium tuberculosis (Mtb), the causative agent of TB, has led to further developments in understanding the physiology of Mtb during infection, as well as searching for novel drug targets, in order to combat the disease. Our understanding of cells, both eukaryotic and prokaryotic, has changed substantially in the last 50 years, incorporating the role of stable and transient protein-protein interactions which govern cell function and behaviour. Although there are many in vivo and in vitro methods for studying protein-protein interactions, they suffer from the lack of ability to distinguish physiological interactions from interactions that occur which are not physiologically relevant to the cell. Structure-based methods for determining protein interactions have the benefit of screening out false positives whilst simultaneously assessing the possible biological function of the protein complex in question. This study sought to assess different high-throughput methods for capturing stable, water soluble protein complexes from M. smegmatis (Msm), a close relative of Mtb, for structural characterisation by low-resolution transmission electron microscopy (EM). The use of partial biochemical fractionation was assessed, which produced low-resolution structures of glutamine synthetase I, bacterioferritin, and Encapsulin. These structures were unambiguously identified through a combination of fitting of homologous crystal structures into the low-resolution maps, and information obtained by liquid chromatography mass spectrometry (LC-MS/MS) of bands isolated from native- and SDS-PAGE gels. Since Encapsulin is likely to participate in the Msm oxidative stress response and functions to enclose the target proteins DyP-type peroxidase (DyP) and ferritin-family protein (BrfB), optimal conditions for cryo-EM were tested for further efforts to obtain a high-resolution structure. Furthermore, hypotheses were generated for the function of Mtb and Msm Encapsulin based on the Msm Encapsulin structure obtained with the aid of a crystal structure homologue; these related to the mode of cargo binding and pore selectivity. A single-step purification method was also assessed through grid blotting on blue native (BN) PAGE using GroEL as a test protein. The hydrophobicity and charge of the EM copper grid was tested to find the optimal grid property for particle transfer. This established that particles of GroEL could be transferred from BN-PAGE onto an EM copper grid and a successful negative stain reconstruction was obtained. In summary, the pipeline from purifying protein complexes to generating hypotheses based on structure was successfully investigated in Msm, which will aid in the production of novel drug targets for Mtb as well as in the application to other organisms.